The adoption of support measures for people with disabilities: the voluntary jurisdiction and the contentious procedure - López Jiménez, Raquel (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The approval of Law 8/2021, 2 June, which reforms the civil and procedure legislation for the support of persons with disabilities in the exercise of their legal capacity, has resulted in the implementation of a new vision of the model of disability in our legal system, as established in the Convention on the Rights of Persons with Disabilities, celebrated in New York on 13 December of 2006, inspired on the mechanisms of support for persons with disabilities. The departure point of this reform is the extinction of the legal regulation in relation to any legal declaration which modifies the legal capacity of persons. In this sense, the implemented system subs titutes the traditional system of representation regarding the decision-making process by the system of aid and support planned in the Convention, being the main concern of this system to look after the willingness, the desire and the preferences of the person with disabilities. To focus on this goal, the former proceedings regarding the modification of the legal capacity through a voluntary jurisdiction proceeding, establishing a special proceeding on the adoption of judicial measures of support. The lawmaker has given a great importance to the voluntary jurisdiction proceedings, placing priority to them over the contentious proceedings under the Spanish procedural law, which has a subsidiary character. The current essay will develop, not intending to exhaust the vast topic, the basis and the legal framework of application to the reform as well as the proceedings of the adoption of specialized support regulated in the Spanish procedural law.